The Association between Prenatal Yoga and the Administration of Ritodrine Hydrochloride during Pregnancy: An Adjunct Study of the Japan Environment and Children's Study. - Yasuyuki Kawanishi; Yasuaki Saijo; Eiji Yoshioka; Yoshihiko Nakagi; Takahiko Yoshida; Toshinobu Miyamoto; Kazuo Sengoku; Yoshiya Ito; Chihiro Miyashita; Atsuko Araki; Reiko Kishi (PLoS ONE, 2016)
While the beneficial effects of prenatal yoga have been reported in recent years, little is known about its effectiveness in pregnant Japanese women. Despite several adverse effects, ritodrine hydrochloride is frequently prescribed to suppress preterm labor in Japan, and its usage may therefore indicate cases of preterm labor. This study aimed to clarify the association between prenatal yoga and ritodrine hydrochloride use during pregnancy.An observational study was conducted as an adjunct study by the Hokkaido unit of the Japan Environment and Children's Study. Information on prenatal yoga practice was collected using a self-questionnaire between March 21, 2012, and July 7, 2015, targeting women who had recently delivered. Ritodrine hydrochloride use was identified from medical records. A total of 2,692 women were analyzed using logistic regression models that adjusted for possible confounders.There were 567 (21.1%) women who practiced prenatal yoga, which was associated with a lower risk of ritodrine hydrochloride use (adjusted odds ratio [OR] 0.77; 95% CI 0.61-0.98). This was especially evident in women with a total practice duration that exceeded 900 minutes throughout their pregnancy (adjusted OR 0.54; 95% CI 0.38-0.76). A sensitivity analysis that excluded patients with threatened abortion during the study period produced similar results.Prenatal yoga was associated with a lower risk of ritodrine hydrochloride use, particularly in women with more than 900 minutes of practice time over the course of their pregnancy. Prenatal yoga may be a beneficial option for pregnant women in the selection of alternative therapies.